Release and re-grasp windows for the kovacs on high bar - Yeadon, M. F.; Stone, B.; Hiley, M. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The aim of the study was to determine the size of the release and re-grasp windows used in the Kovacs release and re-grasp on high bar and compare these to the potential time available to re-grasp the bar. One elite male gymnast performed 10 successful Kovacs (out of 10 attempts) which were recorded using an automatic motion capture system. The release and re-grasp windows were determined from the range of performances and the potential re-grasp window was calculated from the period of time the mass centre was within grasping distance of the bar. The gymnast was very consistent and used a small re-grasp window (23 - 27 ms). The potential re-grasp window was large with the gymnast being within re-grasp distance of the bar for 100 ms prior to grasping the bar. It is likely that the gymnast selected a consistent point within this window for the re-grasp.